Overcoming resistance to anti-PD immunotherapy in a syngeneic mouse lung cancer model using locoregional virotherapy. (2nd January 2018) - Yan, Xiang; Wang, Li; Zhang, Ran; Pu, Xingxiang; Wu, Shuhong; Yu, Lili; Meraz, Ismail M.; Zhang, Xiaoshan; Wang, Jacqueline F.; Gibbons, Don L.; Mehran, Reza J.; Swisher, Stephen G.; et al.
ABSTRACT: Anti-PD-1 and anti-PD-L1 immunotherapy has provided a new therapeutic opportunity for treatment of advanced-stage non-small cell lung cancer (NSCLC). However, overall objective response rates are approximately 15%–25% in all NSCLC patients who receive anti-PD therapy. Therefore, strategies to overcome primary resistance to anti-PD immunotherapy are urgently needed. We hypothesized that the barrier to the success of anti-PD therapy in most NSCLC patients can be overcome by stimulating the lymphocyte infiltration at cancer sites through locoregional virotherapy. To this end, in this study, we determined combination effects of anti-PD immunotherapy and oncolytic adenoviral vector-mediated tumor necrosis factor-α-related apoptosis-inducing ligand (TRAIL) gene therapy (Ad/E1-TRAIL) or adenoviral-mediated TP53 (Ad/CMV-TP53) gene therapy in syngeneic mice bearing subcutaneous tumors derived from M109 lung cancer cells. Both anti–PD-1 and anti–PD-L1 antibodies failed to elicit obvious therapeutic effects in the M109 tumors. Intratumoral administration of Ad/E1-TRAIL or Ad/CMV-TP53 alone suppressed tumor growth in animals preexposed to an adenovector and bearing subcutaneous tumors derived from M109 cells. However, combining either anti–PD-1 or anti–PD-L1 antibody with these two adenoviral vectors elicited the strongest anticancer activity in mice with existing immunity to adenoviral vectors. Dramatically enhanced intratumoral immune response was detected in this group of combination therapy based on infiltrations of CD4+ and CD8+ lymphocytes and macrophages in tumors. Our results demonstrate that resistance to anti–PD-1 immunotherapy in syngeneic mouse lung cancer can be overcome by locoregional virotherapy.